Utilization of waste E plastic particles in cementitious mixtures - Lakshmi, R.; Nagan, S. (Journal of Structural Engineering, 2024)
Ever increasing demand of construction materials has posed new challenges in the environment. Innovative research both in terms of substitute materials as well as effective waste management issues has become inevitable. The properties of concretes containing various E waste plastic particle contents were investigated in this study. Waste E plastic particles were derived from obsolete electrical and electronic equipments. The strength properties of specimens were observed with replacement of coarse aggregate in concrete by E plastic waste in various percentages (4%, 8%, 12%, 16%, 20%, 24% and 28%). Replacement of cement by fly ash (10% by weight) found to improve the properties of E plastic waste concrete. In this study plain cement concrete specimens and E plastic concrete specimens were tested for Compressive strength, Split tensile strength, Flexural strength, Sulphate and Chloride attack. Results showed that E plastic concrete substituted with E plastic waste as partial coarse aggregate replacement despite the variation in the density and strength criteria and that the addition of E plastic particles in concrete up to 15% has a negligible effect on the strength and the selected durability indices.